A study of Co-gasification of sewage sludge and palm kernel shells. (1st March 2021) - Chen, Guan-Bang; Wu, Fang-Hsien; Fang, Tzu-Lu; Lin, Hsien-Tsung; Chao, Yei-Chin
Abstract: In this study, sewage sludge is converted to syngas by co-gasification with palm kernel shells due to their complementary effects. The basic characteristics of fuels are analyzed, and a thermogravimetric analysis integrated with Fourier transform infrared spectroscopy is used to explore the co-pyrolysis/gasification reaction of sewage sludge and palm kernel shells. The results are then used for an FWO activation energy estimation, synergistic effect analysis, and gas yield analysis. The results show that a synergistic effect exists and that sewage sludge in the blended fuel exceeding 30% will increase the CO band, CC bond, C–O, and C–C bond yields. Different synergistic steps are identified, and the average activation energy for the blended fuels is shown to be lower than that in pure feedstocks. A 1 kWth continuous-type fluidized-bed gasifier is designed, and the optimal operating conditions necessary to obtain the maximum H2 /CO ratio and maximum normalized H2 concentration are found through the Taguchi method. The CO2 /(CO2 +H2 O) ratio was the most dominant parameter in the selected conditions, and 70%CO2 /30%H2 O had the best performance. In addition, catalyst addition had the second most dominant effect, where a maximum H2 /CO ratio of 0.563 and a maximum normalized H2 concentration of 32.2% were obtained. Highlights: Co-gasification of sewage sludge (SS) and palm kernel shell (PKS) were studied. SS exceeding 30% will increase the CO band, CC bond, C–O, and C–C bond yields. The activation energy for the blended fuels is lower than that in pure feedstocks. A bubbling fluidized-bed gasifier is used with Taguchi method. The maximum H2 /CO ratio and normalized H2 yield in the syngas were obtained.